Elevated retinal cGMP is not associated with elevated circulating cGMP levels in a canine model of retinitis pigmentosa. - Laurence M Occelli; Kelian Sun; Paige A Winkler; Brandy J Morgan; Simon M Petersen-Jones (PLoS ONE, 2022)
Purpose To investigate whether raised levels of retinal cyclic guanosine monophosphate (cGMP) was reflected in plasma levels in PDE6A-/- dogs. Materials and methods Retina was collected from 2-month-old wildtype dogs (PDE6A+/+, N = 6), heterozygous dogs (PDE6A+/-, N = 4) and affected dogs (PDE6A-/-, N = 3) and plasma was collected from 2-month-old wildtype dogs (PDE6A+/+, N = 5), heterozygous dogs (PDE6A+/-, N = 5) and affected dogs (PDE6A-/-, N = 5). Retina and plasma samples were measured by ELISA. Results cGMP levels in retinal samples of PDE6A-/- dogs at 2 months of age were significantly elevated. There was no significant difference in plasma cGMP levels between wildtype and PDE6A-/- or PDE6A+/- puppies. However, the plasma cGMP levels of the PDE6A-/- puppies were significantly lower than that of PDE6A+/- puppies. Conclusion cGMP levels in the plasma from PDE6A-/- was not elevated when compared to control dogs. At the 2-month timepoint, cGMP plasma levels would not be a useful biomarker for disease.